La fabrique de l’homme objet dans Lolita de Stanley Kubrick - Emmanuelle Delanoë-Brun (Sillages Critiques)
Beyond considerations regarding the degree of continuity or discrepancy between the original work and its filmed version, Stanley Kubrick’s adaptation of Nabokov’s novel fits into a body of cinematographic work that relentlessly probes the question of man’s position in the social, political and intimate sphere, of his often failed aspiration towards selfhood and humanity. Humbert Humbert, as viewed by Stanley Kubrick, appears as yet another representation of the objectified male gradually losing control over the story he at least partially narrates. Still, the character’s progressive dispossession also appears as the condition of his humanistic re-evaluation, in a motion that is characteristic of Kubrick’s constant exploration of the multiple tensions that shape the very definition of humanity, in a paradoxical approach where distance bridges moral, emotional and intellectual gaps, where reiterated contradictions testify to a consistent body of interrogations, where tension, in the end, features as the main condition of humanity.